The use of marine-derived fungi for preparation of enantiomerically pure alcohols - Liu, Hui; de Souza, Fayene Zeferino Ribeiro [UNESP]; Liu, Lan; Chen, Bi-Shuang (Springer Nature, 2018)
A highly enantioselective and minimally polluting approach to optically pure chiral alcohols is developed using cheap, readily available and sustainable marine-derived fungi as catalysts. An evaluation of the synthetic potential of 13 Chinese marine fungi was performed to screen for enantioselective reduction of 13 aromatic ketones from different compound classes as substrates. Good yields and excellent enantioselectivities were achieved with this method. In details, first the effects of several crucial variables on the bioreduction of aromatic ketones with whole cells of marine fungi were explored systematically. Next, we obtained insight into the substrate scope of the tested fungi under the optimized conditions, and selected reduction processes were performed at a commercial scale of up to 1000 mL to determine scalability, which led to excellent yields and enantioselectivities. Last, ketone reductases from two prioritized fungi exhibited good recyclability, with those of Rhodotorula mucilageinosa giving a > 95% yield with up to 99% ee during 3 cycles and those of Rhodotorula rubra giving a > 95% yield with up to 99% ee during 9 cycles.
Keywords: Chiral alcohols; Enantioselective reduction; Marine fungi; Recyclability; Scalability